Strategies For Survival Of Traditional Small And Medium Enterprises In The Digital Age From An Islamic Economic Perspective - Fatimah zahrah Harahap; Marliyah, Marliyah; Harahap, Muhammad Ikhsan (Moneter: Jurnal Keuangan dan Perbankan, 2025)
This qualitative study analyzes the survival strategies of traditional MSMEs in the digital era through a case study of Enrico Pasar Horas Traditional Spice MSME, which has been operating for more than 30 years, using the SOAR (Strengths, Opportunities, Aspirations, Results) analysis method to identify effective strategies for maintaining business existence without comprehensive digital technology adoption. The research findings indicate that SMEs can survive through three main strategies: value-based differentiation rooted in Islamic principles, emphasizing honesty and trustworthiness in maintaining product quality; Islamic relationship marketing that builds long-term relationships based on trust and fairness; and holistic sustainability that integrates economic, social, and environmental responsibilities in accordance with the objectives of Islamic law (maqashid syariah). The implementation of Islamic economic principles such as ash-shidq (honesty), amanah (trust), al-adl (justice), and mas'uliyyah (responsibility) has proven to create a sustainable competitive advantage through financial stability and strong customer loyalty, enabling SMEs to maintain their existence without relying entirely on digital technology in the modern economic transformation.